2015
DOI: 10.3892/ijo.2015.2897
|View full text |Cite
|
Sign up to set email alerts
|

Microarray expression profile of lncRNAs and the upregulated ASLNC04080 lncRNA in human endometrial carcinoma

Abstract: Abstract. Long non-coding RNAs (lncRNAs) have been recognized as a regulator of gene expression, and the deregulation of lncRNAs have been reported to be correlated with carcinogenesis and cancer progression. To explore the function of lncRNA in endometrial carcinoma, we analyzed the expression profiles of lncRNAs and coding genes in 3 paired endometrial carcinoma and adjacent non-tumor tissues, using a microarray. The results of microarray analysis indicated a significant difference in lncRNA and coding gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…According to 17 kinds of differentially expressed lncRNAs, the patients are divided into two major clusters with significantly different progression ( P < 0.001) . Another study found that the expression of 53 kinds of lncRNAs in endometrial carcinoma and adjacent normal tissues are different …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to 17 kinds of differentially expressed lncRNAs, the patients are divided into two major clusters with significantly different progression ( P < 0.001) . Another study found that the expression of 53 kinds of lncRNAs in endometrial carcinoma and adjacent normal tissues are different …”
Section: Discussionmentioning
confidence: 99%
“…20 Another study found that the expression of 53 kinds of lncRNAs in endometrial carcinoma and adjacent normal tissues are different. 21 DLEU1 as a member of the lncRNA family, has been reported to be closely associated with the development and progression of tumors. In Burkitt lymphoma, DLEU1 gene involves in programmed cell death, cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs regulate the expression of genes at the epigenetic, transcriptional, and post-transcriptional levels, and play an important role in physiological processes [Krishnan and Mishra, 2014]. Accumulating evidence indicates that lncRNAs may play complex and extensive roles in promoting the development and progression of cancer [Huarte et al, 2010;Gibb et al, 2011;Sahu et al, 2015], and recent studies showed that lncRNAs play an important role in the development of EC [He et al, 2014, Huang et al, 2014Zhai et al, 2015]. For example, HOTAIR, a well-characterized lncRNA, is upregulated in EC and correlates with poor prognosis [He et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…SNHG12 was first identified in endometrial cancer in a microarray expression profile, and in that study, SNHG12 depletion partly repressed cell proliferation and induced apoptosis [25]. Further studies have shown that SNHG12 is significantly increased in hepatocellular carcinoma and is associated with tumor size, vascular invasion and TNM stage [18].…”
Section: Discussionmentioning
confidence: 99%